Determining the Role of Leadership on Creative Performance by Implementing Synergized-Team Consolidation - Iwan Hermawan; Suharnomo Suharnomo; Sartono Sartono; Gita Hindrawati (AIBPM Publisher, 2022)
This study examines the influence of the role of Leadership (LS) on Creative Performance (CP), which is still inconclusive, with addressing the concept of synergized-team consolidation (STC) as a novelty. STC has the ontology:Â teamwork consolidation into a congruent goal to produce a cohesive-harmonious balance for optimizing creativity output in a work-life point of view such as problem-solving and open innovation. Teamwork is a robust capital for organizations to gain competitive advantage since it will developing qualified human resources through well leadership role. The study employs samples from top management of the fashion industry in Indonesia through survey. Empirical testing using Structural Equation Modeling (SEM) generates equation CP=0.688LS+1.136STC+0.284CL. It concludes that LS has an indirect significant effect on CP through STC as a full mediator. This study solves the gap through STC for space fulfillment of the body of knowledge in the domain of teamwork efficacy. The study emphasizes the significance role of leaders in organizations to synergize teamwork according to their respective expertise in line with the development of the dynamic digital era to increase creativity. It is strongly recommending organizations to utilize recent technology infrastructure to work such as social media as well as facilities for learning through CL.Â Keywords: Leadership, Synergized-team consolidation, Social Media Use to Work, Cyber Learning, Creative Performance